Minat Belajar Mahasiswa Program Studi Administrasi Pendidikan Universitas Jambi Dalam Pemanfaatkan Website E-Learning Semasa Pandemi Covid-19 - Mawardi, Titiana; Sofyan , Sofyan (Program Studi Adminsitrasi Pendidikan Universitas Jambi, 2023)
This study aims to determine the Learning Interest of Jambi University Education Administration Study Program Students in Utilizing the E-Learning Website during the Covid-19 Pandemic and Factors inhibiting their learning interest. This research uses a qualitative approach that is presented descriptively, using a phenomenological approach. Data collection methods using interviews and documents. The results of this study show that: (1) in the utilization of the e-learning website when learning is done well and easily, until the obstacles felt by each student of the Education Administration Study Program through stages: level of convenience, efficiency, memory, errors, and satisfaction. (2) the interest in learning of students of the Education Administration Study Program during the co-19 pandemic includes interest, attention, liking, and student involvement when participating in the learning process. In the learning process when using the e-learning website, students find out and study the e-learning website without coercion. (3) factors inhibiting student interest in learning have a negative impact when learning takes place, inhibiting factors such as laziness, internet connection, learning facilities and lack of supervision in learning during the co-19 pandemic. Â Keywords: learn, e-learning, website, covid, interest